Migrant agency in an institutional context: The Akmola–Astana migration system - Thomas Dufhues; Gertrud Buchenrieder; David Runschke; Susanne Schmeidl; Thomas Herzfeld; Galiya Sagyndykova (Europe-Asia Studies, 2024)
This article addresses one of the key challenges facing transitional and emerging economies: managing rural–urban migration to tackle rural decline and the associated rapid urbanisation. We introduce New Institutionalism as a novel conceptual framework to analyse the interactions between the institutional environment and migrant agency in a rural–urban system: the Akmola–Astana migration system in northern Kazakhstan. Our results suggest that the government might be more successful if it engages migrant agency and incentivises remaining in rural areas instead of designing policies to discourage rural–urban migration.
Keywords: 320